Research Topic Trends In Information And Communication Technology Indexed Science And Technology Index (Sinta) 1 Year 2021 With The Zipf Approach - Via; Nining Sudiar; Vita Amelia (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2023)
ABSTRACT This study aims to find out about the trend topics that are more often discussed in Information & Communication Technology journals indexed by SINTA 1 in 2021 so that they can bring up the latest research subjects. The method used in this research is to use the bibliometric data analysis method based on the zipf rule. The results showed that there was the word "Learning" which was the highest word frequency, which was 317 times appearing with a percentage (3.8%) of the total 8246 words. Then followed by the word "Network" as much as 258 times (3.1%), then "Neural" is a word that appears 235 times or equivalent to (2.8%), the word "System" is also found 160 times, namely with a percentage (1.9%), followed by the word "Machine" 146 times appearing which is equivalent to (1.8%), then the word "Data" also appearing 135 times with a percentage (1.6%), appearing Also the word "Algorithm" is 127 times with a value (1.5%), the word "Image" appears 124 times with a percentage of (1.5%), the word "Energy" is also found 121 times appears with a value (1, 5%) and the top ten words ended with the word “Deep” which appeared 118 times with a percentage (1.4%). These words can be used as keywords in the research article being studied. The calculation above shows that the relevant subject index is greater with the relevant percentage of 62.5%, relevant marginal of 37.5% and irrelevant of 0 %. Keywords : Zipf rules, Bibliometrics, Journals, Articles, Words: Learning   Tren Topik Penelitian Jurnal Teknologi Informasi Dan Komunikasi Terindeks Science And Technology Index (Sinta) 1 Tahun 2021 Dengan Pedekatan Dalil Zipf ABSTRAK Penelitian ini bertujuan untuk mengetahui permasalahan tentang tren topik-topik apa saja yang lebih sering dibahas dalam jurnal Teknologi Informasi dan Komunikasi yang terindeks SINTA 1 pada tahun 2021 sehingga bisa memunculkan subjek penelitian terbaru. Metode yang digunakan pada penelitian ini yaitu menggunakan metode analisis data bibliometrik dengan berdasarkan kaidah zipf. Hasil penelitian ini menunjukkan bahwa terdapat kata “Learning” merupakan frekuensi kata tertinggi yaitu sebanyak 317 kali muncul dengan jumlah persentase (3,8%). Maka dapat diambil kesimpulan bahwa kata tersebut dapat dijadikan sebagai kata kunci (Keyword) pada penelitian artikel yang sedang diteliti. Perhitungan diatas menunjukkan indeks subjek yang nilainya relevan lebih besar dengan jumlah persentase relevan sebesar 62.5%, persentase relevan marginal sebesar 37,5% dan jumlah persentase tidak relevan sebesar 0 %. Keywords: Kaidah Zipf, Bibliometrik, Jurnal, Artikel, Kata: Learning.